Effect of Alkaline Treatment and Fumigation on the Mechanical Properties of Fiber Unsaturated Polyester-Cantula Composite with Compression Molding Method - Salim, Muhamad Saifuddin; Ramadhan, M. Rafidya Bintang; Fanani, Elvira Wahyu Arum; Ariawan, Dody; Surojo, Eko (Mekanika: Majalah Ilmiah Mekanika, 2022)
This research examines the strength of the Unsaturated Polyester Resins (UPRs)-Cantala composite with the addition of filler Microcrystalline Cellulose (MCC). Composites were created with a Volume Fraction (VF) of 30% and a 45° angle. This angle variation received the same treatment as the others, including untreated, alkaline, and fumigation. The treatment time for alkali treatment was six hours, while the treatment time for fumigation was 10 hours. The strength of each angle variation was determined, as well as its treatment of tensile strength, modulus of elasticity, and Poisson ratio UPRs-Cantala composites. According to the results, the alkali treatment produced the highest tensile strength and modulus of elasticity values. The highest Poisson ratio value was discovered without treatment at a 45°. The alkaline treatment yielded the highest tensile strength and modulus of elasticity test results. The pullout fiber fracture dominated the untreated composite fracture, whereas the fiber breakage fracture dominated the alkaline treatment.